Sintering behavior of Ni–Zn ferrite powders prepared by molten‐salt synthesis. Issue 6 (17th July 2021) - Yang, Pao; Qi, Hongbin; Fu, Xiuli; Peng, Zhijian
Abstract: Ni0.5 Zn0.5 Fe2 O4 powders were prepared by a novel molten‐salt synthesis method. The effects of calcination processes of the powders on their sintering behaviors were investigated. Compared with the synthesis by traditional solid‐state reaction, the proposed molten‐salt method can significantly reduce the synthesis temperature of Ni0.5 Zn0.5 Fe2 O4 from 800 to 550°C below, and the prepared powders have relatively high sintering activity at low temperature, which can thus decrease the sintering temperature. However, the abnormal growth of grains is easy to occur during sintering, thus resulting in uneven grain size. In particular, during the molten‐salt synthesis, the holding time for calcination is a dominant factor affecting the activity and crystallization degree of the resultant powders. From the point of view of increasing the density of sintered bodies, the optimal conditions for synthesizing Ni0.5 Zn0.5 Fe2 O4 powder by the proposed molten‐salt synthesis is 400°C for 6 h. In addition, the saturate magnetization of the finally obtained ferrite ceramics has nothing to do with the preparation processes, while their coercivity depends on their densification and grain size caused by their different processing routes.